Hubungan Tingkat Stres dengan Siklus Menstruasi pada Siswi Putri Kelas 3 di SMA Pondok Karya Pembangunan Jakarta Islamic School Jakarta Timur Tahun 2022 - Novriyanda, Nova (Universitas Bengkulu, 2023)
Adolescence is one of the stages in human life which is often called puberty, namely the transition period from children to adulthood. Every young woman will experience physical and psychological changes, these changes include all of her developments that are experienced as preparation for entering adulthood. The occurrence of this big change is generally confusing for teenagers who experience it. Menstrual disorders are common and if not treated can affect the quality of life and daily activities. This study aims to determine the relationship between stress levels and the menstrual cycle in grade 3 female students at SMA Pondok Karya Pembangunan Jakarta Islamic School. Correlative Descriptive Research with a Cross Sectional Approach to Grade 3 female students at SMA Pondok Karya Pembangunan Jakarta Islamic School. The sampling technique was carried out by means of accidental sampling with a total of 77 respondents. This research instrument uses a questionnaire. The statistical test used is the Chi-Square test that this research can be trusted with an error rate of 0.05. The majority of respondents experienced severe stress levels of 59.7%, the majority of respondents had abnormal menstrual cycles of 53.2%, the majority of respondents experienced premenstrual syndrome of 92.2% of the total respondents. The results showed that there was a relationship between stress levels and the menstrual cycle with a p-value of 0.036. Most of the 3rd grade female students at SMA Pondok Karya Pembangunan Jakarta Islamic School experience severe stress with abnormal menstrual cycles. There is a relationship between stress levels and the menstrual cycle. For young women it is hoped that as much as possible to avoid stress so that the menstrual cycle is not disturbed while for health workers to increase the provision of information to young women related to reproductive health, especially about the menstrual cycle and the factors that influence it.